Indigenous Workforce Participation at a Mining Operation in Northern Australia - Pearson, Cecil; Daff, S. (National Institute of Labour Studies, 2013)
The potential of the Australian minerals industry to generate considerable national revenue can be jeopardised in periods of economic growth by fostering a shortage of relevant educated and skilled personnel. Legal reforms of the 1990s, public pressure, and benefits by employing local Aboriginal people has driven the installation of work-integrated learning programs designed to reduce the skill shortage by increasing the employment rate of Indigenous people in the mining industry. This article reports five years of primary data to detail nationally accredited attainments and relevant job outcomes of an Indigenous education-vocation program that has delivered sustainable jobs in a substantive remote mining operation in Northern Australia. Identified barriers for applicants and vocational career choices that are framed by values and priorities held by regional Indigenous people are discussed to focus on a conclusion challenging the mining industry and the government to disclose how Indigenous training schemes are ameliorating the skills gap in the Australian mining industry.